Training and Hedonic Survey Test of Lemon Candy Using Natural Sweetener from Sugarcane Water as an Odors - Fadhillah, Nurul; Surbakti, Chemayanti; Lubis, Muhammad Fauzan; Juwita, Nur Aira (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Lemon candy is a candy that has a combination of sweet and sour taste. In making lemon candy using several ingredients. One of them is using natural ingredients. Plants that can be used as ingredients for making candy are lemon juice and sugarcane juice. This community service activity involved class XI HKBP Sidorame Private High School students which was based on product innovation in the form of lemon candy with a combination of the two natural ingredients above. The purpose of this activity is to determine the level of preference (hedonic) for a product in the form of lemon candy with a combination of lemon juice and sugarcane juice. The activity begins with making a product in the form of lemon candy from a combination of lemon juice and sugarcane juice. The activity continued with data collection using pre-test, post-test and hedonic test questionnaires. The results of filling out the pre-test showed that SMAS HKBP Sidorame students' knowledge regarding lemon candy was still lacking with the percentage of yes answers to each question namely 100%, 33.33%, 20%, 6.67%, 40%. The results of filling out the post-test showed that SMAS HKBP students' knowledge was very good with the percentage of yes answers to each question namely 100%, 77%, 97%, 93%, 93%. This shows the development and increase in knowledge of SMAS HKBP Sidorame students about lemon candy. The results of the hedonic test survey obtained the highest percentage for shape parameters of 33.33% (very like), color of 43.3% (quite like), aroma of 40% (like very much), hardness of 30% (very like) and taste of 46.67% (very like). These results indicate that SMAS HKBP Sidorame students like the preparation of lemon candy.